Modified semi-circular bend test to determine the fracture toughness of anisotropic rocks. (15th May 2019) - Nejati, Morteza; Aminzadeh, Ali; Saar, Martin O.; Driesner, Thomas
Abstract: The conventional semi-circular bend (SCB) test of anisotropic rocks, with symmetric loading, generates a Mixed-Mode I / II crack tip loading when the crack is not aligned with one of the principal material directions. This paper presents a modified SCB test for anisotropic rocks to ensure a pure Mode I crack tip loading. It is demonstrated that the stress intensity factor (SIF) solution of an anisotropic SCB specimen depends on two dimensionless parameters, the anisotropy ratios of the Young's modulus and apparent shear modulus, as well as the anisotropy orientation. These two dimensionless parameters are selected since they have physical meaning, and are generally bounded for rock materials. Based on these anisotropy parameters, the semi-circular test is modified to configure pure Mode I, or tensile stress at the crack tip, by using an asymmetric three-point bend configuration. Extensive finite element analyses are performed to obtain the span ratio and normalized SIF of the SCB specimen with different anisotropy ratios and orientations.